2016
DOI: 10.1002/bjs.10055
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in life-threatening military injury and the associated risk of infective complications

Abstract: Background Tranexamic acid (TXA) has been shown to reduce mortality from severe hemorrhage. Although recent data suggest that TXA has anti-inflammatory properties, few analyses have investigated the impact of TXA on infectious complications in trauma patients. We examined the association between TXA administration and infection risk among injured military personnel. Methods Patients administered TXA were matched by injury severity score to patients who did not receive TXA. Conditional logistic regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Another possible modification is decreasing the number of red blood cell transfusions by using post-injury tranexamic acid, an anti-fibrinolytic agent that has been shown to decrease mortality in bleeding trauma patients [40,41], or using younger blood products or blood product alternatives. It is not clear if any of these interventions would affect infection rates, however, one retrospective analysis that compared military trauma patients who did and did not receive tranexamic acid reported no significant association between tranexamic acid and infection risk [42].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible modification is decreasing the number of red blood cell transfusions by using post-injury tranexamic acid, an anti-fibrinolytic agent that has been shown to decrease mortality in bleeding trauma patients [40,41], or using younger blood products or blood product alternatives. It is not clear if any of these interventions would affect infection rates, however, one retrospective analysis that compared military trauma patients who did and did not receive tranexamic acid reported no significant association between tranexamic acid and infection risk [42].…”
Section: Discussionmentioning
confidence: 99%
“…Later, et al showed that in patients undergoing cardiac surgery, patients receiving TXA and EACA showed less upregulation of pro-inflammatory genes and more upregulation of anti-inflammatory genes relative to patients not receiving these medications (95); however, they found no effects on cytokine or growth factor concentrations (96). Lewis and colleagues examined this issue retrospectively in military trauma patients; their results demonstrated no increased risk for infection, and further showed no decrease in time to infection in patients receiving TXA relative to those who had not, suggesting that early immune suppression in TXA-treated patients is not present (97). The ongoing Tranexamic Acid Mechanisms and Pharmacokinetics in Traumatic Injury (TAMPITI) trial is specifically focused on downstream immune effects following TXA administration, and should shed more light on this issue (98).…”
Section: Conmentioning
confidence: 99%
“…There were 13 retrospective studies,1621,23–25,27,30,31,33 five prospective observational studies,22,26,28,29,32 and one randomized controlled trial 34. Ten studies2226,2932,34 reported administering TXA as given in the CRASH-2 trial (1 gram [g] intravenous [IV] bolus followed by 1 g IV over eight hours); three studies16,20,21 reported giving TXA 1 g bolus (without the maintenance dose), and six studies1719,27,28,33 did not report TXA dosing. Three studies17,27,34 administered TXA within eight hours from the time of injury (as done in the CRASH-2 trial), 12 studies16,18,2126,2932 administered TXA primarily within three hours from the time of injury, and four studies19,20,28,33 did not report the timing of TXA administration.…”
Section: Resultsmentioning
confidence: 99%